The Influence of Self-Control and Financial Planning Behavior on Financial Risk Attitude and Online Loan Decisions, with Financial Stress as a Moderating Variable - Miftahul Huda; Nur Ajizah; Sri Wahyuni (Lembaga Bale Literasi, 2026)
This study examines the influence of Self Control and Financial Planning Behaviour on Financial Risk Attitude and online loan decision making, with Financial Stress as a moderating variable in the context of digital financial services. The rapid growth of financial technology has increased access to online lending and raised concerns about irrational financial decisions. This study aims to analyze how psychological and behavioral factors influence financial decisions in using online loans. A quantitative explanatory approach was used with data collected from 200 respondents in Surabaya through questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling. The results show that Financial Planning Behaviour has a positive and significant effect on Financial Risk Attitude and online loan decisions, while Self Control and Financial Risk Attitude do not have significant effects. Financial Stress significantly moderates the relationship between variables and online loan decisions. In conclusion, financial planning is a key factor in rational decision making, while Financial Stress influences behavior in digital financial contexts.